Impact of an annular solar eclipse on trace gases and meteorological parameters over Jaipur, Northwestern India - Prakash, Divya; Verma, Sunita; Payra, Swagata; Kumar, Vivek (Frontiers in Environmental Science, 2022)
This study aimed to identify the impact of annular solar eclipse i.e. 21st June 2020 on variation of meteorological parameters along with trace gases using statistical analyses. The study site is located in Poornima University, Jaipur (26.7796° N, 75.8771° E), Rajasthan.The observational analysis indicates a rapid decrease in solar direct radiation (SDR) which varied between 706 W/m2 to 79 W/m2 during the eclipse. SDR reduced to 79 W/m2 at the maximum peak of solar eclipse at 11:55 AM at study location. The comparative analysis shows the variation of SDR during the solar eclipse, day before and day after the event. A strong dip was observed in SDR during annular eclipse day with respect to before (734.31 W/m2) and after (734.375 W/m2) eclipse event. Furthermore, the impact of solar eclipse on temperature (Ts) and Relative Humidity (RH) was analyzed over Jaipur. The statistical analyses demonstrate an apparent decrease in temperature of about 2°C while RH shows a slight increment (3.45 %) during the solar eclipse event. The results show an inverse correlation between solar eclipse and trace gases variations during the eclipse due to the changes in solar radiation, surface temperature, variation in winds that might affect the photochemical processes.